Factor XIII Subunit A Immunohistochemical Expression is Associated With Inferior Outcomes in Acute Promyelocytic Leukemia. Issue 3 (March 2018) - Raval, Jay S.; Berg, Aaron N.; Djokic, Miroslav; Roth, Christine G.; Rollins-Raval, Marian A.
Abstract : Coagulation factor XIII subunit A (FXIIIa) intracellular expression has been described in platelets, megakaryocytes, monocytic cells, and leukemic blasts. Flow cytometric-based studies have suggested prognostic implications of FXIIIa expression, especially within the acute promyelocytic leukemia (APL) subgroup of acute myeloid leukemia (AML); however, its prognostic correlate by immunohistochemistry (IHC) is unknown. The aims of this study were to (1) define the clinicopathologic features of FXIIIa IHC-positive AML and (2) compare APL with other AML subtypes. Eighty-seven bone marrow biopsies or clot/particle preparations from our institution were evaluated with FXIIIa IHC. The study cohort consisted of bone marrow evaluations of 36 consecutive pretherapy APL, 42 selected pretherapy non-APL AML, and 9 negative staging cases. FXIIIa IHC expression was correlated with clinical and pathologic features and overall survival (OS). Leukemic blast FXIIIa cytoplasmic positivity was noted in 56% (20/36) APL and 74% (31/42) non-APL AML ( P =0.10). FXIIIa IHC expression was associated with inferior OS within the APL cohort ( P =0.04). No OS differences were noted in comparing FXIIIa IHC expression in all AML ( P =0.17), or FXIIIa IHC expression within favorable, intermediate or adverse cytogenetic groups ( P =0.14, 0.22 and 0.87, respectively). FXIIIa IHC expression is observed among a broad spectrum of AML subtypes and is not characterized by specific pathologic features. However, within the APL subgroup, FXIIIa IHC expression is associated with an inferior outcome and may be useful for additional prognostic risk stratification.